BioChroma - A New and Patented Technology for Processing Radioactive Wastewater from Nuclear Medicine Therapy Facilities in Hospitals and Clinics - José Rodríguez (World Journal of Nuclear Medicine)
After undergoing radionuclide therapy, patients generate wastewater with a considerable amount of radioactivity, which can reach levels of as much as 90% of the administered dose. Due to the risk of accumulation after discharge into the sewer, it is advisable to collect this effluent for its treatment prior to final discharge. Delay and decay (natural decomposition of the isotope) is the most commonly used technical method of abating radioactive iodine, but it is frequently criticized as being complex and very expensive. BioChroma is a technology that has been developed as an alternative to these complicated and expensive systems. This paper describes this new technology and presents, as an example, a system that was installed and successfully commissioned in the middle of 2008 in a nuclear medicine ward with 12 beds in Stuttgart (Germany). Based on existing legislation, the responsible authorities and the company that operated the hospital agreed on a maximum activity level of 5 Bq/l. If a typical delay and decay system would have been installed, the 180 m³ treatment plant that was already available in the hospital cellar would have to be extended by additional 150 m³. By implementing the patented BioChroma process, the space requirements were reduced by 75%. For instance, since the new system was integrated into the existing installation, tanks accounting for 120 m³ could be used as buffering volume in the new wastewater treatment plant. The operation of the referred plant is currently producing very good results with values below the specified limit of 5 Bq/l for the isotope 131 I. In addition, 90 Y has been reported to be eliminated at the same time. Over the past 2 years of operation, the wastewater treatment plant has been able to achieve a maximum processing capacity of more than 2,000 l/day, which equates to a nuclear medicine ward with approx. 20 beds. The highest level recorded during the test period (of 180 days after start-up) was a peak of nearly 2,800 l/day.